Wetland in science education: A systematic literature review (SLR) - Parham Saadi; Misbah Misbah; Rossy Arlinda; Nurlaela Muhammad; Muhdi Harto; Qamariah Qamariah; Surya Haryandi (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: This study investigates and describes the wetland environment in science education from 1998 to 2024 using the PRISMA method, analyzed with one bibliometric technique, co-occurrence.Aim: This Systematic Literature Review (SLR) aims to synthesize several studies related to the wetland environment in science education. Therefore, this research focuses on “Wetland Environment in Science Education”.Method: The methods used include article selection, inclusion criteria, and more objective analysis methods. The PRISMA article selection steps, known as the PRISMA flow diagram, recommended for SLR, resulted in 76 articles and journals.Result: A bibliometric review was conducted on journals related to the wetland environment in science education, yielding 20 interrelated articles discussing the wetland environment in science education. This data was then visualized using VOSviewer.Conclusion: The extracted articles concluded that there is a significant relationship between the wetland environment and other variables, particularly in science education.